Evaluasi Pengelolaan Obat Antibiotik di Puskesmas dalam Mendukung Program Pengendalian Resistensi Antimikroba - Aisyah Qinthara Nabila Putri; Rasmi Zakiah Oktarlina; Ayu Tiara Fitri; Juspeni Kartika (Pusat Riset dan Inovasi Nasional, 2026)
Antimicrobial resistance (AMR) represents a serious global health threat caused by the irrational use of antibiotics. In Indonesia, this issue has become more complex due to the high rate of antibiotic purchases without prescriptions and weak distribution control. This study aims to evaluate the effectiveness of antibiotic management in community health facilities, particularly Puskesmas, and to identify factors influencing antibiotic use practices in support of the national antimicrobial resistance control program. A qualitative method with a literature study approach was used, reviewing national and international scientific sources, including WHO reports, the Indonesian Ministry of Health, and the National Action Plan for Antimicrobial Resistance Control (RAN-PRA) 2020–2024. The findings show that approximately 41% of antibiotics are still obtained without prescriptions, and 70.75% of pharmacies in Indonesia continue to sell antibiotics freely. Both public and healthcare workers’ awareness of AMR remains low, as antibiotics are often misused for viral infections. Although national policies such as RAN-PRA adopt a One Health approach, their implementation still faces challenges, including limited resources, weak monitoring, and regional disparities. Puskesmas plays a strategic role in education, supervision, and reporting on antibiotic use but requires capacity strengthening and intersectoral collaboration. This study concludes that AMR control demands synergy among government, medical professionals, academics, and the public through enhanced education, stricter antibiotic distribution control, and evidence-based policymaking. Continuous efforts are essential to preserve antibiotic effectiveness and strengthen Indonesia’s national health resilience against global antimicrobial resistance threats.